(untitled) (Revista de Historia, 2025)
Consejo Editorial Maiten Franco y Gastón Montesino Directores Consejo de Edición Andrea Rodríguez (Universidad Nacional del Comahue); Rocio Belén Martínez (Universidad Nacional del Comahue) Rolando Bonato (Universidad Nacional del Comahue); Marta Flores (Universidad Nacional del Comahue); Sabrina Aguirre (Universidad Nacional del Comahue); Cecilia Allemandi (Universidad Nacional del Comahue). Secretaría de Edición Gastón Montesino (Universidad Nacional del Comahue) Comité Académico Omar Acha (Universidad de Buenos Aires – CONICET), Argentina; Samuel Amaral (Universidad Nacional Tres de Febrero), Argentina; Waldo Ansaldi (Universidad Nacional de La Plata), Argentina; Susana Bandieri (Universidad Nacional del Comahue – CONICET), Argentina; Marta Bonaudo (Universidad Nacional de Rosario – CONICET), Argentina; Atilio Boron (FLACSO), Argentina; Gerardo Caetano (Universidad de la República), Uruguay; Lila Caimari (Universidad de San Andrés), Argentina; Guillermo Mira Delli-Zotti (Universidad de Salamanca), España; Orietta Favaro (Universidad Nacional del Comahue), Argentina; Enrique Mases (Universidad Nacional del Comahue), Argentina; María Estela Spinelli (Universidad Nacional del Centro de la Provincia de Buenos Aires), Argentina; Maristella Svampa (Universidad de Buenos Aires – CONICET), Argentina; César Tcach (Universidad Nacional de Córdoba – CONICET), Argentina; Sergio Grez Toso (Universidad de Chile), Chile.